1977
DOI: 10.1172/jci108749
|View full text |Cite
|
Sign up to set email alerts
|

Urinary kallikrein and plasma renin activity as determinants of renal blood flow. The influence of race and dietary sodium intake.

Abstract: A B S T R A C T We investigated the relationship of the kallikrein-kinin system and the renin-angiotensin system in the regulation of blood pressure, salt and water excretion, and renal blood flow. Normotensive and hypertensive black and white men were studied during unrestricted sodium intake as well as on a 10-meq/day sodium intake; potassium intake was held constant throughout the study (80 meq/day).During unrestricted sodium intake, urinary kallikrein activity was greater in white normotensives than white … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
88
2
1

Year Published

1979
1979
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 233 publications
(99 citation statements)
references
References 32 publications
8
88
2
1
Order By: Relevance
“…Moreover, low PRA has also been found in blacks on diets where the intake of sodium has been carefully controlled and lower PRA has been found on both low and high sodium intakes. 6,12 By contrast, several studies 9,13,46,47 have reported a lower urinary potassium excretion in blacks. And although this has not been confirmed in every comparative study, 36,48 a lower potassium intake could be important as changes in potassium intake, though to a smaller extent, can also influence renin release largely through the impact on sodium balance.…”
Section: Dietary Sodium and Potassium Intakementioning
confidence: 92%
See 2 more Smart Citations
“…Moreover, low PRA has also been found in blacks on diets where the intake of sodium has been carefully controlled and lower PRA has been found on both low and high sodium intakes. 6,12 By contrast, several studies 9,13,46,47 have reported a lower urinary potassium excretion in blacks. And although this has not been confirmed in every comparative study, 36,48 a lower potassium intake could be important as changes in potassium intake, though to a smaller extent, can also influence renin release largely through the impact on sodium balance.…”
Section: Dietary Sodium and Potassium Intakementioning
confidence: 92%
“…However, 'low renin hypertension' is clearly an arbitrary definition and the actual frequency in blacks has ranged widely depending on the cut-off value taken to delimit the state of 'low PRA'. Furthermore, suppressed PRA is also present in both normotensive and hypertensive blacks even when on a low salt diet 6,12 and in response to loss of sodium as induced by administration of diuretics. 23,24 The low PRA in blacks is also associated with a lower plasma angiotensin II independent of ACE activity.…”
Section: Journal Of Human Hypertensionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, we studied three ethnic groups from widely differing geographic sites of ancestry (Europe, sub-Saharan Africa, and east Asia), since previous reports on kallikrein excretion have not directly compared more than two such groups. 1,8,9,11,20 Reports over the past two decades have demonstrated substantial ethnic differences in renal kallikrein excretion, 2,6-9 with African-Americans displaying consistently lower kallikrein activity than Caucasians. Here we found a substantial diminution in urinary kallikrein excretion in African-Americans (Table 1; F = 5.3, P = 0.006), but no difference (P = 1.0) between Caucasian and Asian values.…”
Section: Ethnicitymentioning
confidence: 99%
“…Finally, previous carefully controlled studies, with fixed and comparable dietary exposures, have clearly documented ethnicity as a determinant of kallikrein excretion, especially in studies comparing African-Americans and Caucasians. 11,20 How (mechanistically) might potassium have influenced the ethnic variations in kallikrein excretion in our sample? One likely mediator is aldosterone, since potassium directly stimulates aldosterone biosynthesis and release from the adrenal cortex zona glomerulosa 8,34 and kallikrein is an aldosterone responsive target in man.…”
Section: Potassium: Role and Mechanismmentioning
confidence: 99%